The Effect of Ease of Use and Organizational Support on Digital HR System Acceptance with Employee Digital Readiness as a Moderating Variable - Wafiqah Setyawati Wahyuni (Publikasi Indonesia, 2026)
Digital transformation in human resource management has encouraged organizations to implement Digital Human Resource (HR) Systems to improve the efficiency and effectiveness of HR management. However, the success of such implementation depends not only on technological sophistication but also on user acceptance. This study examines the effects of System Ease of Use and Organizational Support on Digital HR System Acceptance and investigates the moderating role of Digital Readiness. A quantitative explanatory design was employed. Primary data were collected through a five-point Likert-scale questionnaire distributed to 114 employees of Inside Job, selected using purposive sampling, and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with SmartPLS 4. The findings indicate that System Ease of Use (B = 0.331; t = 4.502; p = 0.000) and Organizational Support (B = 0.254; t = 3.609; p = 0.000) have positive and significant effects on Digital HR System Acceptance. Digital Readiness was also found to strengthen the effects of both System Ease of Use (B = 0.290; t = 3.562; p = 0.000) and Organizational Support (B = 0.297; t = 3.607; p = 0.000) on Digital HR System Acceptance. The research model explains 52.2% of the variance in Digital HR System Acceptance (R² = 0.522). These findings suggest that successful Digital HR System implementation requires an integrated strategy involving simplified system design, strong organizational support, and continuous improvement of employees' digital readiness.